Composite based polymeric displays: an introduction to a new smart engineering approach to incorporate transition metals to the polymer matrix. (1st January 2003) - Talaie, A.; Lee, Y.K.; Jang, J.; Choo, D.J.; Park, S.M.; Lee, J.Y.; Park, S.H.; Huh, G.; Taguchi, T.; Maeder, E.
In this paper, we report on the production and characterisation of polymeric composites for display device applications. Polymeric compositebased electroluminescence devices (PCELD) were developed using a metaldoped organic layer as an electron-injecting layer. Using transition metals including Ni, Fe and Cu as a dopant and MEH-PPV (Poly(2-Methoxy, 5-(2′-Ethyl-hexyloxy)-P-Phenylenevinylene)) as the emitter layer, we studied the photoluminescence (PL) intensity of the doped polymer by incorporation of metals in two different ways. These were physical incorporation (laser ablation) and chemical incorporation (mixing). It was found that Fe can improve the PL intensity of undoped polymer if the laser ablation process was carried out for different periods of time. However, the PL intensity decreased when the mixing method was used with different concentrations of the transition metals.